Factors associated with the double burden of malnutrition at the household level: A scoping review. Issue 25 (1st September 2022) - Guevara-Romero, Edwin; Flórez-García, Víctor; Egede, Leonard E.; Yan, Alice
Abstract: The double burden of malnutrition (DBM) at the household level has been defined as the coexistence of underweight children and overweight mothers within the same household. The objective of the scoping review was to identify and understand factors associated with DBM. We conducted the scoping review of published, peer-reviewed journal articles in two major databases used in public health research (PubMed and Web of Science). A total of 70 articles met the eligibility criteria. The following factors were identified: mother's age, height, educational level, occupation, food intake, breastfeeding, family income, family size, and urbanization type. Overall, results were heterogeneous. Two scenarios have been identified. The first scenario is those obese women with a job, having a sufficient income, a high educational level, the ability to purchase food, and live either in rural or urban areas. The second scenario is obese women without a job, having an insufficient income, a low educational level, without the ability to purchase food, and live either in rural or urban areas. The DBM at the household level is a complex public health problem. There is a need for target-specific interventions to address child undernutrition and maternal overweight/obesity simultaneously.